2020
DOI: 10.3390/insects11110806
|View full text |Cite
|
Sign up to set email alerts
|

Functional Response and Intraspecific Competition in the Fall Armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae)

Abstract: Functional responses of the fall armyworm (FAW) larvae at each stage, and their intraspecific competition associated with cannibalism, provide insights into developing pest management strategies for the FAW. To help use insecticides more sparingly, the functional response and intraspecific competition of the FAW larvae were evaluated under the laboratory conditions. The results showed that all stages of the FAW larvae displayed a type II functional response to diet. Based on Holling’s disc equation, the search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Therefore, the rating recorded at 14 DAI provides actual host plant and insect pest interaction reflecting the complete leaf damage caused due to FAW and also the response of the host plant against the FAW infestation. Moreover, the feeding rate of earlier instars (First and second) is very less (Ren et al, 2020 ) and this might be the reason for the low rating of 7 DAI. The released neonate larvae become fourth to fifth instar feed heavily by the time when data are taken at 14 DAI resulting in higher damage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the rating recorded at 14 DAI provides actual host plant and insect pest interaction reflecting the complete leaf damage caused due to FAW and also the response of the host plant against the FAW infestation. Moreover, the feeding rate of earlier instars (First and second) is very less (Ren et al, 2020 ) and this might be the reason for the low rating of 7 DAI. The released neonate larvae become fourth to fifth instar feed heavily by the time when data are taken at 14 DAI resulting in higher damage.…”
Section: Discussionmentioning
confidence: 99%
“…Spodoptera frugiperda (Lepidoptera: Noctuidae) is a polyphagous pest known as the fall armyworm that, during its larval stage, can attack more than 353 plant species of 76 families, including economically important crops such as maize, soybean, cotton, sorghum, and wheat [1]. Despite its being predominantly found in Latin American countries [2], studies have shown occurrences in African and Asian countries and, more recently, in Australia [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, the infestation of S. frugiperda can affect the native biodiversity by reducing both native insect pests and other insect communities (Sokame et al 2021b;Sokame et al 2021a). Larvae of S. frugiperda have the ability to compete (intraspecies competition) and predate other larvae (cannibalism) (Chapman et al 2000;Ren et al 2020). S. frugiperda larvae can also reduce the larvae of other lepidopteran pests through interference competition and predation (Wiseman and McMillian 1969;Song et al 2021).…”
Section: Introductionmentioning
confidence: 99%